Pengaruh Model TGT Berbantuan Media Wordwall terhadap Penguasaan Materi Bangun Datar : The Effect of TGT Model Assisted by Werdwall Media on Mastery of Shape Material - Suardipa, I (Widyadewata, 2025)
This study aims to compare the TGT Model assisted by Wordwall with conventional learning in grade IV students of SD Gugus II Buleleng. Using a quasi-experimental design with a pretest-posttest control group, this study involved 84 students. The research sample was taken using the sample random sampling method, with SDN 2 Tukadmungga as the experimental group (29 students) and SDN 1 Pemaron as the control group (22 students). Data were obtained through observation, interviews, tests, and documentation, then analyzed using SPSS version 25.0 for Windows. Data analysis includes validity test, reliability test, test difference test, item difficulty level test, N-Gain test, normality test, homogeneity test, and t-test. Based on the hypothesis that has been evaluated, data analysis using the independent t-test shows that t count> t table, namely the t count value of 8.165> t table 1.676. This shows that there is a difference in students' understanding of the flat shape material of Team Games Tournament learning equipped with Wordwall media with conventional learning